STIG study: real-world data of long-term outcomes of adults with Pompe disease under enzyme replacement therapy with alglucosidase alfa - Gutschmidt, Kristina (J Neurol, 2021)
BACKGROUND: Pompe disease is one of the few neuromuscular diseases with an approved drug therapy, which has been available since 2006. Our study aimed to determine the real-world long-term efficacy and safety of alglucosidase alfa. METHODS: This multicenter retrospective study (NCT02824068) collected data from adult Pompe disease patients receiving ERT for at least 3 years. Demographics and baseline characteristics, muscle strength, lung function (FVC), walking capability (6MWT), and safety were assessed once a year. Evaluation was done on the group and individual levels, using quantitative linear models (t test) and general univariate linear models (ANOVA). FINDINGS: Sixty-eight adult Pompe disease patients from four countries (Spain, Taiwan, Italy, Germany (STIG)) participated. The mean follow-up was 7.03 years ± 2.98. At group level in all outcome measures, an initial improvement followed by a secondary decline was observed. After 10 years, the 6MWT(%pred) showed the most sustained positive effect (p = 0.304). The MRC(%max) remained stable with a mild decline (p = 0.131), however, FVC(%pred) deteriorated significantly (p < 0.001) by 14.93% over 10 years of ERT. The progression rate of FVC(%pred) under ERT could be explained in most of the patients (83.5%) by the disease severity at baseline. Furthermore, our study shows a decline in the FVC combined with an increase in non-invasive and invasive ventilation requirements in adult Pompe disease patients over time. CONCLUSIONS: The STIG real-world study confirms an initial efficacy of ERT in the first years with a secondary sustained decline in multiple outcome measures. Further efforts are required to establish a more valid long-term monitoring and improved therapies. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00415-021-10409-9.